Fungal Endophyte Communities in Begonia Species from the Brazilian Atlantic Rainforest - Correia, Ana M. L. [UNESP]; Lira, Simone P.; Assis, Marco A. [UNESP]; Rodrigues, Andre [UNESP] (Springer Nature, 2018)
Tropical plants represent hotspots of endophytic fungal species diversity. Based on culture-dependent methods, we evaluated the endophytic fungal communities in leaves of three plant species found in the Brazilian Atlantic Rainforest: Begonia fischeri, Begonia olsoniae, and Begonia venosa. These species are found in two distant sites: a continental region and an insular area. A total of 426 fungal endophytes in 19 genera were isolated in pure culture including Colletotrichum (51.6% of isolates) and Diaporthe (22.5%) as the most abundant, followed by Phyllosticta (3.5%), Neopestalotiopsis (1.8%), Stagonospora (1.8%), and Nigrospora (1.6%) among the genera found in minor abundance. The diversity and composition of fungal taxa differed across plant hosts. Richness and diversity of fungi were higher in B. fischeri in comparison to B. olsoniae and B. venosa. Discriminatory analysis revealed that fungal communities are structured according to hosts, which means that each plant species had its distinct endophytic communities, but dominated by common fungal taxa. This is the first study to report fungal endophytes in begonia leaves and characterize their communities.
Keywords: Begoniaceae; Diversity; Endophytic; Fungus–plant interaction